Inventarisasi Hama Persemaian Di Hutan Tanaman Rakyat Desa Ngambur Kecamatan Bengkunat Belimbing Kabupaten Lampung Barat - Ikro Fajar Surachman; Indriyanto Indriyanto; Agus M. Hariri (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Forest pest inventory is research activity to gather and arrange the data of pests existing in seedling periode. Pest inventory activites are used to determine pest types, the number and crop damage order to apply appropriate control. This research was aimed to identity the pest types and its attack levels at community plantation forest nursery. This research was conducted at Community Plantation Forest in Ngambur Village of Bengkunat subdistrict, West Lampung on April to May 2012. The collected data was identified taxonomically. The data was included of pest types, pest density, attack levels, and demages. All samples were collected using systematic method in diagonal pattern. The results was obtained 9 types in kadam nurseries, white albizia, and umbrella tree, which caterpillars (Daphnis hypothous), locust (Locusta migratoria),moths (Hyblaea puera), bag worm (Pteroma plagiophelps), bug (Cosmoleptrus sumatranus), mealy bug (Planococcus citri), leaf caterpillar (Doleschallia polibete), yellow butterfly (Eurema spp.), snail (Achatina fulica) and 1 type of insect predators that weaver ants (Oecophylla smaragdina). Insect population was high enough but not damage the plant nursery while the most dangerous insect pest was a bag worm (Pteroma plagiophelps) and moth (Hyblaea puera). Bag worm larvae cause severe damage, the loss on the leaves. The extent of damage by insect pests classified in the category of still mild attacks. Pest control can be done mechanically or chemically. Keywords: community plantation forest, inventory of pests, Lampung, nursery